Open range [videorecording (DVD)] - Costner, Kevin; Duvall, Robert; Bening, Annette; Gambon, Michael (Touchstone Home Entertainment, 2004)
Boss Spearman, a rugged old-timer, free grazes cattle. He and Charley have been partners for ten years. The pair and their employees, Mose and Buttons, are driving their cattle across the West. Mose is attacked and thrown in jail during a visit to a town. The local cattle rancher, Baxter, wants the free grazers off his land and when Boss and Charley retrieve Mose, they are warned that they have until the next day to be out of the area. Charley confesses his past as a killer during the Civil War and strikes up a tentative romance with Sue, the sister of the town doctor.